ORGANIZE TECHNOLOGY EDUCATION LESSONS DIDACTIC CONDITIONS OF LEARNING - Z. R. Isaqova; Kochkarova Shahzadabegim; Khoshimova Umidakhan; Hakimova Mavludakhon (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the didactic conditions and current situation of the organization of technology education classes are disclosed. Education of the young generation requires great responsibility and knowledge from pedagogues. The methodical activity of the teacher is of great importance in the development of science.